The impact of social media usage and addiction among student / Siti Maheran Mohd Faudzi - Mohd Faudzi, Siti Maheran (Universiti Teknologi MARA Cawangan Selangor, 2019)
The social network, which is one of the key indicators of the technology era, attracts all levels while virtual worlds over real life through the applications it offers. Especially young people show high interest in social media that is an extension of Internet technology. Social media addiction is increasing worldwide. This study aims to examines impact of academic performance in social media addiction among social student. Based on data obtained by the Malaysian Communications and Multimedia Commission (MCMC, 2016), shows that Malaysia’s broadband penetration rate reaches almost 78 percent. The study also found that those who are still in school spend the most time online, which is 20.9 hours a week. This this study. The two theories, the diffusion of innovations theory and the process virtualization theory posited that impact social media usage and addiction towards academic performance in student university.